2021
DOI: 10.1128/aem.02684-20
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics of Antimicrobial and Heavy Metal Resistance in the Cecal Microbiome of Fattening Pigs Raised without Antibiotics

Abstract: This study aimed to detect the cecal microbiome, antimicrobial resistance (AMR) and heavy metal resistance genes (MRGs) in fattening pigs raised under antibiotic-free (ABF) conditions compared with ordinary industrial pigs (control, C) using whole-genome shotgun sequencing. ABF pigs showed the enrichment of Prevotella (33%) and Lactobacillus (13%), whereas Escherichia coli (40%), Fusobacterium and Bacteroides (each at 4%) were notably observed in the C group. Distinct clusters of cecal microbiota of ABF and C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 64 publications
5
37
0
Order By: Relevance
“…Captivity and free-range are the main rearing condition for sika deer, and it is valuable to evaluate how the present practices affect environmental antibiotic resistance transmission. Unlike the composition of gut microbiota, the predominant phyla in antibiotic-resistant bacteria were Firmicutes and Proteobacteria (rather than Firmicutes and Bacteroidetes ), indicating that Proteobacteria played a more important role in the abundance of ARGs than Bacteroidetes ( 36 ). We found abundant antibiotic resistances in the fecal microbiome of sika deer, and tet Q and lnu C dominated the AROs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Captivity and free-range are the main rearing condition for sika deer, and it is valuable to evaluate how the present practices affect environmental antibiotic resistance transmission. Unlike the composition of gut microbiota, the predominant phyla in antibiotic-resistant bacteria were Firmicutes and Proteobacteria (rather than Firmicutes and Bacteroidetes ), indicating that Proteobacteria played a more important role in the abundance of ARGs than Bacteroidetes ( 36 ). We found abundant antibiotic resistances in the fecal microbiome of sika deer, and tet Q and lnu C dominated the AROs.…”
Section: Discussionmentioning
confidence: 99%
“…According to the RDA of tetracycline resistance, tet Q, tet X, and tet W/N/W were related to the dominant genus Prevotella in the captive deer. Previous studies have reported that tet Q genes can be isolated from Prevotella strains in sick and healthy humans ( 36 , 39 ). lnu C is a lincosamide resistance gene, which is induced by clindamycin and lincomycin ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a new addition to the UK market, it is unknown how consumers perceive 'raised without antibiotics' labelled products and whether the presence of such labels influence food choice. Research surrounding 'raised without antibiotics' labels in the UK has been exclusively based on analytical techniques, focusing on the identification of food-borne pathogens in 'raised without antibiotics' labelled foods (Tunsagool et al, 2021). Thus, to the best of our knowledge, this is the first study of its kind to investigate consumer knowledge and perceptions towards antimicrobial use in agriculture and willingness to buy 'raised without antibiotics' labelled meat.…”
Section: Introductionmentioning
confidence: 99%
“…This also explains why the number (115 ARGs) and diversity of ARGs detected in the present study was much lower than in a previous study (250 ARGs) using the same short reads that were used to assemble the MAGs here (11) as well as in the metagenome co-assembly (897 ARGs; data not shown). Despite the limitations associated with ARG binning we were able to provide genomic context for 115 ARGs including several that are relatively abundant in the swine gut such as erm(B), tet (44), tet(Q), and tet(W) (35)(36)(37)(38).…”
Section: Many Of Thementioning
confidence: 99%